Hermeneutics of The Oenames Tribe Regarding Hau Monef as a Symbol of Patriarchal Cultural Religiosity in The Border Region of Indonesia and East Timor - Tamelab, Petrus; Bele, Graciana Amanda; Martasudjita, Emananuel Pranawa Dhatu (Universitas Sanata Dharma, 2026)
Each tribe has its own perspective on divinity or the supreme being. Therefore, the procedures for establishing a relationship with the supreme being also differ. Long before Catholicism was introduced by missionaries to the archipelago, traditional communities had unique procedures for establishing a relationship with the supreme being. The method used in this study is the literature method. The author studied library literature and linked it to the traditional practices of the Oenames tribe. The purpose of this study was to examine in greater depth the Oenames tribe's understanding of hau monef as a symbol of patriarchal religiosity. The results of the study show that members of the Oenames tribe believe that hau monef is a symbol of the presence of the Supreme Being through their ancestors. Therefore, whenever tribe members ask for blessings or permission from their ancestors, a ritual is always performed on hau monef. This shows that there is an unbroken relationship between the ancestors and the living members of the tribe. In conclusion, the Oenames tribe has a strong vertical paradigm of the supreme being, which is represented by the symbol of hau monef. Hau monef is a place for prayers and for giving thanks for all the blessings received by tribe members. Hau monef is not just a ritual artefact but a symbol of the presence of the Supreme Being, which Oenames tribe members believe has an impact on their safety and livelihood.